Increased prefrontal activity and reduced motor cortex activity during imagined eccentric compared to concentric muscle actions - Olsson, CJ; Hedlund, Mattias; Sojka, Peter; Lundström, Ronnie; Lindström, Britta (Frontiers in Human Neuroscience, 2012)
In this study we used functional magnetic resonance imaging (fMRI) to examine differences in recruited brain regions during the concentric and the eccentric phase of an imagined maximum resistance training task of the elbow flexors in healthy young subjects. The results showed that during the eccentric phase, pre-frontal cortex (BA44) bilaterally was recruited when contrasted to the concentric phase. During the concentric phase, however, the motor and pre-motor cortex (BA 4/6) was recruited when contrasted to the eccentric phase. Interestingly, the brain activity of this region was reduced, when compared to the mean activity of the session, during the eccentric phase. Thus, the neural mechanisms governing imagined concentric and eccentric contractions appear to differ. We propose that the recruitment of the pre-frontal cortex is due to an increased demand of regulating force during the eccentric phase. Moreover, it is possible that the inability to fully activate a muscle during eccentric contractions may partly be explained by a reduction of activity in the motor and pre-motor cortex.